PENGARUH BRAND PERSONALITY, BRAND AWARENESS DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BUKU DI GRAMEDIA BENGKULU - Rezky, Reza Muhammad (UM. Bengkulu, 2024)
The title of this research is The Influence of Brand Personality, Brand Awareness and Product Quality on Book Purchasing Decisions at Gramedia Bengkulu. This research is based on the importance of the right system and strategy in conveying messages to consumers through marketing media which usually uses one or a combination of marketing variables. Many factors can influence purchasing decisions, including brand personality, brand awareness and product quality. This research aims to determine the influence of Brand Personality, Brand Awareness, product quality on product purchasing decisions at the Gramedia Store, Bengkulu City. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all consumers of the Gramedia Store, Bengkulu City, Bengkulu. This research used an incidental sampling technique with a sample of 150 respondents. The data collection techniques include interviews, observation, literature study, and questionnaires. Based on the results of research using multiple regression data analysis techniques, it was found that brand personality, brand awareness and product quality together show an influence on consumer purchasing decisions at Gramedia Bengkulu Keywords: Brand Personality, Brand Awareness, Product Quality, Purchase Decision